Implementing Green Transformational Leadership to Provide Sustainable Organizational Performance - Yanto Ramli; Dudi Permana; Aldina Shiratina; Erna Sofriana Imaningsih (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: The intention of this research is to increase concern about the environment and the demands of sustainable environmental practices that have encouraged and resulted in high demands for environmental practices in Indonesia. Purpose: This research will conduct four research variables to explore the co-relation between the variables in order to examine the potential influence of the said variables such as green transformational leadership, green human resource practices, employee green behavior and sustainable organization environment. Design/methodology/approach: The methodological tool used to analyze the data was partial least squares. Data were collected using questionnaires distributed in Jakarta, Indonesia. This was a descriptive and a verification study.Findings/Results: The results show that green transformational leadership has a significant influence on green human resource practices compared to employee green behavior, which has a more significant influence on sustainable organizational performance than green human resource practices.Conclusion: The implementation of Green Human Resource Practices and Employee Green Behavior as intervening factors enriches the understanding of the complex relationship between green transformational leadership styles, organizational sustainability, and employee behaviors in a green organizational context. Originality/value (State of the art): The state of the art of this research is by implementing Green Human Resource Practices and Employee Green Behavior as the Intervening variable to examine the influence of Green Transformational Leadership on Sustainable Organizational Performance, whereas in previous research, the variables of Green Human Resource Practices and Employee Green Behavior were treated as the independent variables. Keywords: green transformational leadership, green human resource practices, employee green behavior, sustainable organizational performance